2015
DOI: 10.2147/ndt.s87703
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversities and laboratory pain perception

Abstract: Childhood adversity has frequently been related to a wide range of psychosomatic complaints in adulthood. The present study examined the relationship between different forms of childhood adversity and laboratory measures of pain. Heat pain tolerance and perceived heat pain intensity were measured in a community-based sample of 62 women (aged 20–64 years). Participants completed the Childhood Trauma Questionnaire (CTQ), which assesses five forms of childhood adversity: physical abuse, sexual abuse, emotional ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 51 publications
2
15
3
Order By: Relevance
“…No ACE was associated with heat pain intensity (Pieritz, Rief & Euteneuer, 2015). We found no statistically significant effect of resilience on any type of CNCP and on disabling CNCP respectively in multivariate analysis.…”
Section: Comparison With Other Studiescontrasting
confidence: 62%
“…No ACE was associated with heat pain intensity (Pieritz, Rief & Euteneuer, 2015). We found no statistically significant effect of resilience on any type of CNCP and on disabling CNCP respectively in multivariate analysis.…”
Section: Comparison With Other Studiescontrasting
confidence: 62%
“…Research has previously shown that childhood trauma, in terms of emotional or physical abuse, is related to chronic pain [ 19 , 20 ]. In particular, laboratory research on pain perception has suggested that traumatic experiences in childhood are associated in particular with the affective, but not sensory, components of pain [ 21 ]. Though of paramount importance, the specific association between interpersonal touch experiences valued as negative and affective touch, still needs to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…All these methods are quite different from the pain induced with the used pressure algometer.Hence, further methods should be taken into account for the assessment of pain tolerance in future research. A further explanatory approach could be that the experience of adversities such as child abuse does not lead to the assumed habituation but rather to an increased sensitivity to painful events, due to neurobiological alterations(Pieritz, Rief, & Euteneuer, 2015) Pieritz et al (2015). found a negative relationship of emotional abuse with heat pain tolerance in a population-based sample of women.…”
mentioning
confidence: 99%